Enhancing the social environments of elderly nursing home residents: are high rates of interaction enough? - Carstensen, L L (1986)
We investigated the social validity of a common intervention (i.e., serving food during a social hour) that has been reported to facilitate social interaction among nursing home residents. Using a group reversal design, rates of interaction were measured. In addition, the vocal content of the interactions was recorded and coded by raters blind to condition. Rates of interaction more than doubled during the treatment phases, but ineffective vocal behavior accounted for the bulk of the increase. Results suggest the need to examine the utility of such programs in nursing homes.